Successful treatment of refractory palmoplantar pustulosis by upadacitinib: report of 28 patients - Du, Na; Yang, Jingyi; Zhang, Yiwen; Lv, Xinyan; Cao, Lei; Min, Wei (Frontiers in Medicine, 2024)
Background Upadacitinib, a specific JAK1 inhibitor, has minimal effect on other JAK subtypes. It influences the inflammatory process in various ways. Upadacitinib has been approved for conditions such as rheumatoid arthritis, psoriatic arthritis, atopic dermatitis, and ulcerative colitis in various countries. The purpose of this study is to assess the clinical efficacy and safety of upadacitinib in patients with refractory palmoplantar pustulosis who have not responded to conventional treatments (e.g., Acitretin, Tripterygium wilfordii Hook F, cyclosporine, methotrexate). Methods We conducted a retrospective collection of clinical data from 28 patients who received upadacitinib treatment at the Department of Dermatology, First Affiliated Hospital of Suzhou University, from July 2022 to December 2023. We evaluated the Palmoplantar Pustulosis Area and Severity Index (PPPASI) scores, Dermatology Life Quality Index (DLQI) scores, and Physician’s Global Assessment (PGA) scores before and after treatment. We also recorded any adverse events during the treatment process. Results A total of 28 patients were diagnosed with PPP, including 10 males and 18 females, and 8 patients (3 males and 5 females) were diagnosed with SAPHO syndrome. The mean age was (36.3 ± 10.5) years. After 12 weeks of treatment, PPPASI scores decreased from baseline (13.86 ± 2.76) to (5.56 ± 1.08), with a statistically significant difference (p < 0.05). DLQI scores decreased from (12.55 ± 4.56) to (2.03 ± 1.13), also showing a statistically significant difference (p < 0.05). Additionally, 20 patients achieved a PGA score of 0/1. No severe adverse events were reported during the treatment and follow-up period. Conclusion Upadacitinib could be an additional safe and effective treatment for treating refractory palmoplantar pustulosis with a potential benefit on patients’ quality of life. Further studies are needed to assess its short-and long-term efficacy and safety in larger sample sizes in randomized double-blind controlled trials.